Rumus Bilangan Reproduksi Dasar Covid-19 dengan Adanya Vaksinasi Dosis 1 dan 2 - Aini Fitriyah (Limits: Journal of Mathematics and Its Applications, 2022)
This study aims to determine the basic reproduction number for Covid-19 with vaccination. The research method used is a literature study. The research step begins with construct a mathematical model of Covid-19 with vaccination, determining the basic reproduction formula and simulation. The mathematical model of Covid-19 is constructed by distinguishing susceptible subpopulations that have vaccinated doses 1 or 2, as well as infected subpopulations that have been vaccinated or not before. The model is . The analysis shows that the basic reproduction formula consists of several types of parameters. It is in accordance with simulation by using Matlab software. Simulation was taken based on Covid-19 and vaccination data in the Central Java Province. It shows that the greater the value of individual being vaccinated, the lower the basic reproduction number. This means that Covid-19 can disappear if more individuals get vaccinated against Covid-19.